Stakeholder Analysis in the Development of Saba Budaya Baduy - ., Ardiyansah; Farida, Naili; Warsono, Hardi; ., Kushandajani (KnE Social Sciences, 2022)
Developing countries in the Asian region use cultural tourism to boost their economies. One of the traditional village tours on the island of Java that still upholds ancestral values is that of the Baduy indigenous people. The development of Saba Budaya Baduy involves collaboration between the government, the private sector and universities, but the form of cooperation that is carried out is not optimal and involves a pattern of asymmetry or imbalance in the roles of each stakeholder. This study aimed to analyze the role of stakeholders in the development of Saba Budaya Baduy. A qualitative approach was used and interviews were conducted with the Baduy indigenous people and other stakeholders. The results demonstrated that there were different levels of roles in stakeholders. Based on the category groups, the government was the key stakeholder; businesses, universities, and the Baduy indigenous people were the primary stakeholders; and NGOs and the mass media were secondary stakeholders. The government element was in quadrant I (key players); elements of academics, the private sector, and indigenous people were in quadrant II (context setters); NGO elements were in quadrant III (subjects); and elements of mass media were in quadrant IV (crowd). Relationships with the government could involve complementarity and cooperation. The relationship between the government and the private sector could take the form of conflict, complementarity, or cooperation. The relationship between the government and universities could involve complementarity or cooperation. Relations with NGOs could take the form of cooperation. The relationship between the government and mass media could involve complementarity or cooperation, and the relationship between the government and indigenous people could be in the form of conflict, complementarity, or cooperation. Keywords: stakeholder analysis, Saba Budaya Baduy, Baduy indigenous people